Alcohol Brief Intervention in a university setting: A small-scale experimental study. (June 2017) - McClatchey, Kirstie; Boyce, Mandy; Dombrowski, Stephan U
Alcohol misuse among university students is commonplace. This study aimed to assess whether Alcohol Brief Intervention would be effective in reducing hazardous alcohol consumption in students compared to an alcohol information leaflet. Participants ( n  = 125) assessed as higher risk drinkers using the Alcohol Use Disorders Identification Test Consumption were randomly assigned to receive an Alcohol Brief Intervention ( n  = 67) or an information leaflet ( n  = 58), with 82 (66%) completing a follow-up assessment. Alcohol consumption ( F (1, 80) = 14.52, p  < 0.001) and the Alcohol Use Disorders Identification Test Consumption scores ( F (1, 80) = 23.63, p  < 0.001) significantly decreased in both groups post-intervention; however, the groups did not significantly differ. Further research is recommended.